2020
DOI: 10.1111/eip.13070
|View full text |Cite
|
Sign up to set email alerts
|

Toolkit for assessing and addressing cognitive health in early psychosis: Evaluation of feasibility and utility in a coordinated specialty care setting

Abstract: Aim Methods to identify and harness individual cognitive strengths while addressing relative weaknesses have the potential to complement recovery services for first‐episode psychosis but systematic implementation is needed. We developed a cognitive health toolkit, trained teams from OnTrackNY, a network of coordinated specialty care (CSC) programs and examined toolkit feasibility and clinical utility during the first year of roll‐out. Methods The toolkit includes a clinician manual, assessment and decision‐mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The current study provides some insights into the cognitionfocused treatments that young people with mental illness may find (Allott, van-der-el, et al, 2020); however, few trials have tested the effectiveness of compensatory interventions with young people, especially those with high prevalence conditions. Notably, research in early psychosis settings, which often serve a high proportion of young people with cognitive impairment, has found that compensatory interventions and psychoeducation are considered by clinicians to be the most feasible treatments to deliver (Saperstein et al, 2020;Saperstein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study provides some insights into the cognitionfocused treatments that young people with mental illness may find (Allott, van-der-el, et al, 2020); however, few trials have tested the effectiveness of compensatory interventions with young people, especially those with high prevalence conditions. Notably, research in early psychosis settings, which often serve a high proportion of young people with cognitive impairment, has found that compensatory interventions and psychoeducation are considered by clinicians to be the most feasible treatments to deliver (Saperstein et al, 2020;Saperstein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While this observation may partly explain the discrepancy between the young people's cognitive needs and the provision of suitable treatments, it may also highlight a need for further workforce development. Supporting clinicians to routinely conduct cognitive screening and implement strategies with young people may be an important first step in addressing this need (Bryce & Allott, 2019; McIntyre et al, 2019; Saperstein et al, 2020; 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the US Food and Drug Administration’s black box warning of increased risk of death when antipsychotics are used by people with dementia directly contradicts recommendations for first-line treatment of schizophrenia. In the absence of evidence-based guidance on pharmacologic treatment strategies, an innovative approach is a cognitive health toolkit that provides materials for assessment and service planning . Additional research is needed to determine evidence-based pharmacotherapies for individuals with schizophrenia who develop dementia.…”
Section: Discussionmentioning
confidence: 99%